Rapid Structure Determination of Ranitidine Hydrochloride API in Two Crystal Forms Using Microcrystal Electron Diffraction - Yokoo, Hidetomo; Aoyama, Yoshitaka; Matsumoto, Takashi; Yamamoto, Eiichi; Uchiyama, Nahoko; Demizu, Yosuke (Chemical & pharmaceutical bulletin, 2024)
The solid-state properties of drug candidates play a crucial role in their selection. Quality control of active pharmaceutical ingredients (APIs) based on their structural information involves ensuring a consistent crystal form and controlling water and residual solvent contents. However, traditional crystallographic techniques have limitations and require high-quality single crystals for structural analysis. Microcrystal electron diffraction (microED) overcomes these challenges by analyzing difficult-to-crystallize or small-quantity samples, making it valuable for efficient drug development. In this study, microED analysis was able to rapidly determine the configuration of two crystal forms (Forms 1, 2) of the API ranitidine hydrochloride. The structures obtained with microED are consistent with previous structures determined by X-ray diffraction, indicating microED is a useful tool for rapidly analyzing molecular structures in drug development and materials science research.